Integrated Nutrient Management Strategies to Improve Yield and Quality of Strawberry Fruits - Yadav, S K; Khokar, U U; Homa, Fozia (Journal of Postharvest Technology, 2014)
People all over the world prefer strawberry for its attractive colour, pleasant  flavour, and richness in vitamins and minerals. Berries are highly perishable  and mainly used for the table purpose. Hence, quality attributes play very  important role in determining economic viability of its commercial cultivation. A field study was conducted in Himachal Pradesh (India) to standardize  integrated nutrient management (INM) strategy through suitable combination  of various organic, inorganic and biological nutrient sources to achieve higher  productivity of quality berries. Total recommended doses of organic and  inorganic fertilizers (50 t ha-1 farmyard manure and 80, 40, 40 kg ha-1 of N,  P2O5 and K2O, respectively) were converted in terms N, P and K. The nutrient  requirements were supplied through different combinations of organic and  inorganic sources (50% organic and 50% inorganic or 100% inorganic) with  and without Azotobacter inoculation. Inorganic nitrogen was applied at one or  two at the stages of establishment of plant and before flowering.
Keywords: Vermicompost; Azotobacter; Fruit grades; Integrated nutrient; management (INM)